Why Do Science Lecturers Distinguish the Use of Mobile Technologies for Instruction? - Onojah, Amos Ochayi; Obielodan, Omotayo Olabo; Onojah, Adenike Aderogba; Alani, Taye Rasheed (Indonesian Journal of Curriculum and Educational Technology Studies, 2022)
Lecturers are not engaging in the frequent use of mobile technologies to support and supplement instructions and their learning experiences, as these technologies assist in simplifying concepts and could lead to improved academic performance. The objectives were to investigate science lecturers' perceived use of mobile technologies for instruction. The study was a descriptive research of survey type and a random sampling technique was adopted to select 172 respondents. Data were analyzed using frequency count, percentage and t-test. The findings established that science lecturers have a bright perception of the use of mobile technologies for instruction. The study concluded that science lecturers’ perception of the use of mobile technology boosts their students’ learning. It was thus recommended that government should provide an affordable platform for lecturers and students to have their personal technological devices (computer set) which they can use independently and for group learning. Abstrak Dosen tidak sering menggunakan teknologi seluler untuk mendukung dan melengkapi instruksi dan pengalaman belajar mereka, karena teknologi ini membantu menyederhanakan konsep dan dapat meningkatkan kinerja akademik. Tujuannya adalah untuk menyelidiki dosen sains yang menggunakan teknologi seluler untuk pengajaran. Penelitian ini merupakan penelitian deskriptif dengan tipe survey dan teknik random sampling digunakan untuk memilih 172 responden. Analisis data menggunakan frekuensi hitung, persentase dan uji-t. Temuan menetapkan bahwa dosen sains memiliki persepsi yang cerah dalam penggunaan teknologi seluler untuk pengajaran. Studi ini menyimpulkan bahwa persepsi dosen IPA tentang penggunaan teknologi seluler meningkatkan pembelajaran siswa mereka. Oleh karena itu, direkomendasikan agar pemerintah menyediakan platform yang terjangkau bagi dosen dan mahasiswa untuk memiliki perangkat teknologi pribadi (perangkat komputer) yang dapat mereka gunakan secara mandiri dan untuk pembelajaran kelompok.